The practical experience of consulting in school quality improvement program: Process and reflection - Kakhai, Kuncharee (Journal of Rattana Bundit University, 2020)
The School Quality Improvement Program is a large-scale program covering 201 schools with four educators acting as a consulting team. The theories in consulting are based on systematic theory and social structure theory; expanded into learning, coaching and consulting. It was found that 41% of the schools were the good practices and 16 % of them were the poor practices. From practical experiences; it was found that 1) initially, the sensitive point of the consultation is the identification of surface problems not real ones, and 2) the changes consisted of planned changes, opportunity created changes and emerged changes. The critical success techniques are knowledge sharing, listening attentively, questioning, demonstrating, knowledge-based practicing and periodically reflecting to develop the next step of the program.